Study on The Causes of Flooding in Batang Mahat, Lima Puluh Kota Regency, West Sumatera - Junaidi Junaidi; Darwizal Daoed; Diva Syandriaji (Green Engineering Society, 2023)
This research is located in Batang Mahat Lima Puluh Kota Regency, about 9.26 km2 from the narrowing location at Batu Kisok to the upstream, prone to flood. Due to several flooding events in Batang Mahat, various assumptions and hypotheses have emerged regarding the causes of Batang Mahat flooding. This research analyses the causes of flooding in Batang Mahat using Steady Flow simulation in HEC-RAS 6.2 software. The result implies that two factors caused the flood: (1) The channel capacity is insufficient to accommodate flood water discharge, where the simulation results shown at the Q50 discharge (2003.07 m3/s) flood inundated several areas in cross-sections upstream and tributary. (2) The impact of the narrowing location at the river channel in Batu Kisok, which is shown by the simulation of a decrease in water elevation at eight cross-sections at the upstream and two cross-sections at the tributary after the cross-sections in Batu Kisok are widened from ±30 m to ±45 m (50%), ±60 m (100%), and ±75 m (150%).